Effects of Combined Laparoscopic Cystectomy and Leuprolide Acetate Therapy on Anti-Mullerian Hormone Level and Antral Follicle Count Profile in Endometriosis - Usman, Fatimah; Hilmawan, Bagus; Yusuf, Kemas; Manan, Heriyadi; Theodorus, Theodorus; Andrina, Hana (Indonesian Journal of Obstetrics & Gynecology Science, 2023)
Objective: This study examines the effectiveness of combined laparoscopic cystectomy and leuprolide acetate therapy on AMH level and AFC profile in endometriosis.Method: This study is a randomized controlled clinical trial with open label form. The subjects were divided into control and therapy groups, with the therapy group receiving leuprolide acetate injection following laparoscopic cystectomy. In both groups, the AMH levels and AFC were examined prior to the surgery and six weeks after before they were compared.Results: There were significant pre-post differences of AMH levels(p = 0.000) and AFC (p = 0.000) in the therapy group but not in the control group. In the therapy group, the mean increases of AMH level and AFC were 0.94 (95% CI: 0.63-1.25) and 9.53 (95% CI: 6.83-12.24), respectively. Linear regression model found that AFC level prior to intervention was a significant predictor of endometriosis ASRM grade (p = 0.001) with an R-value of 0.633, suggesting strong correlation.Conclusion: The combined therapy of laparoscopic cystectomy and leuprolide acetate injection for endometriosis provided better outcome concerning ovarian reserve, as opposed to the therapy with laparoscopic cystectomy alone. Peran Kombinasi Laparoskopi Kistektomi dan Terapi Leuprolide Asetat Terhadap Kadar Hormon Anti-Mullerian dan Profil Jumlah Folikel Antral pada Penderita EndometriosisAbstrakTujuan:Studi ini bertujuan menguji keefektifan kombinasi kistektomi laparoskopi dan terapi leuprolide acetate terhadap kadar AMH dan profil AFC pasien endometriosis.Metode: Penelitian ini merupakan uji klinis terkontrol acak dengan bentuk open label. Subjek dibagi menjadi kelompok kontrol dan terapi, dengan kelompok terapi menerima injeksi leuprolide acetate setelah kistektomi laparoskopi. Pada kedua kelompok, kadar AMH dan AFC diperiksa sebelum pembedahan dan enam minggu setelahnya sebelum kemudian dibandingkan.Hasil: Terdapat perbedaan bermakna kadar AMH (p = 0,000) dan AFC (p = 0,000) sebelum dan sesudah pada kelompok terapi tetapi tidak pada kelompok kontrol. Pada kelompok terapi, rata-rata peningkatan kadar AMH dan AFC adalah masing-masing 0,94 (95% CI: 0,63-1,25) dan 9,53 (95% CI: 6,83-12,24). Model regresi linier menemukan bahwa kadar AFC sebelum intervensi merupakan prediktor signifikan derajat endometriosis sesuai ASRM (p = 0,001) dengan nilai R sebesar 0,633 yang menunjukkan korelasi yang kuat.Kesimpulan: Terapi kombinasi kistektomi laparoskopi dan injeksi leuprolide acetate untuk endometriosis memberikan hasil yang lebih baik terhadap cadangan ovarium, dibandingkan dengan terapi dengan kistektomi laparoskopi saja.Kata kunci: endometriosis; leuprolide acetate; kistektomi; hormon anti-mullerian; jumlah folikel antral